The Role of Hyperbaric Oxygen Therapy in Pneumatosis Cystoides Intestinalis—A Scoping Review - Alpuim Costa, Diogo; Modas Daniel, Pedro; Vieira Branco, João (Frontiers in Medicine, 2021)
Pneumatosis cystoides intestinalis (PCI) is characterised by gas-filled cysts within gastrointestinal tract wall from oesophagus to rectum, with preferential involvement of large and small intestine. PCI is rare with an estimated incidence of 0.03 to 0-2% in general population. PCI can be distinguished into idiopathic (15%) or secondary (85%) and the clinical picture ranges from completely asymptomatic to life-threatening intraabdominal complications. Although aetiology of PCI appears to be multifactorial, the exact pathophysiology is poorly understood and two main theories have been proposed (mechanical and bacterial). Over the last decades, an enormous therapeutic armamentarium was considered in PCI’s management, including hyperbaric oxygen therapy (HBOT). Treatment comprises conservative treatment in mild cases to surgery in highly symptomatic and complicated PCI. In the late 70s, HBOT started to be used in selected cases of PCI not responding to conservative measures. Since then, several case reports, case series, and reviews have been published in the literature with variable outcomes. The overall response rate and complete response were 92.1% (n= 82/89) and 65.2% (n= 58/89), respectively, with a median follow-up of 7 months. Furthermore, HBOT is extremely safe, with few reported complications in the literature when used for PCI. Nevertheless, a randomised, controlled, and double-blind clinical trial is unlikely to occur given the rarity of PCI, logistical issues of HBOT, and methodological considerations related to adequate blinding with a sham-controlled group. HBOT in combination with personalised diet and antibiotics may be beneficial for moderate to severe PCI in patients with no indication for emergency exploratory laparotomy. The purpose of this article is to synthesize the existing data, analyse results of previous studies, identify gaps in knowledge, and discuss PCI’ management, including the proposal of an algorithm, with a special focus on HBOT.